Perbandingan Pelaksanaan Struktur Beton Sistem Cast In Situ Dan Precast Terhadap Biaya Dan Waktu Pelaksanaannya (Studi Kasus : Proyek Pembangunan Rumah Susun Provinsi Sulawesi Selatan, Jalan Poros Sa’dan (Kampus II UKI Toraja) - Yulius Pakiding (Departement of Mathematics Education, 2022)
Along with the rapid development of the times, at the same time the construction industry has also grown rapidly. Along with the development of that era, the technology and construction methods in the world are increasingly developing. This also applies in Indonesia, construction methods in Indonesia are also developing. One form of the development of construction methods in Indonesia is the precast construction method. This study aims to determine how much the costs and how long it takes to implement the Cast In Situ and Precast Methods of columns and beams.The method used in this research is a quantitative method using the calculation of SNI 7394: 2008